A comparative study on the service profiles and practice facilities among urban general practices in east and west Malaysia - Khoo, E.M. (2000)
1171 urban general practices in East and West Malaysia were compared regarding their service profiles and practice facilities. In general, practices in both parts put important emphasis on preventive health care. More practices in East Malaysia were providing hormone replacement therapy and sexually transmitted diseases services but less were providing intrapartum care, counselling services including sexual and marital counselling and problems associated with social deviance such as alcohol and drug abuse. Although most practices in East Malaysia were solo practices, they were more comprehensive in terms of the provision of practice facilities when compared to those in West Malaysia. A greater number of them had ultrasound facilities, peak flow meters, ECG machines, computers and blood biochemistry facilities.